The effect of maleinized linseed oil (MLO) on mechanical performance of poly(lactic acid)-thermoplastic starch (PLA-TPS) blends. (20th August 2016) - Ferri, J.M.; Garcia-Garcia, D.; Sánchez-Nacher, L.; Fenollar, O.; Balart, R.
Highlights: Thermoplastic starch offers partial miscibility with PLA as evidenced by FESEM. The addition of 4–6 phr MLO leads to an elongation at break of 140–160%. MLO also provides a compatibilization effect. Abstract: In this work, poly(lactic acid), PLA and thermoplastic starch, TPS blends (with a fixed content of 30 wt.% TPS) were prepared by melt extrusion process to increase the low ductile properties of PLA. The TPS used contains an aliphatic/aromatic biodegradable polyester (AAPE) that provides good resistance to aging and moisture. This blend provides slightly improved ductile properties with an increase in elongation at break of 21.5% but phase separation is observed due to the lack of strong interactions between the two polymers. Small amounts of maleinized linseed oil (MLO) can positively contribute to improve the ductile properties of these blends by a combined plasticizing-compatibilizing effect. The elongation at break increases over 160% with the only addition of 6 phr MLO. One of the evidence of the plasticizing-compatibilizing effect provided by MLO is the change in the glass transition temperature (Tg ) with a decrease of about 10 °C. Field emission scanning electron microscopy (FESEM) of PLA-TPS blends with varying amounts of maleinized linseed oil also suggests an increase in compatibility.